Orientação ao consumidor e performance financeira : uma análise do papel da capacidade de inovação de produto - Santos, Mirela Jeffman dos (2014)
Increasing dynamism that has been self configuring in the marketing environment, in relation not only to market transformations but also to technological evolutions, had mobilized researchers to investigate how organizations work in presence of unstable conditions and what are the factors that lead to high levels of performance. In this context, the most noticeable ones are the strategic orientations that had been intensively investigated in strategic marketing area last decades. Nevertheless, the theory has pointed strategic orientations as direct antecedents of performance and does not take into account the capabilities development which makes the organization able to transform resources and to apply the knowledge to produce superior value in the market. To contribute to the literature in the area, the present study analyzes the relationships among Consumer Orientation (CO), Product Innovation Capacity (PIC) and Financial Performance (FP) in influence of Technological Turbulence (TT). In this way, it was suggested that in presence of high levels of TT, PIC mediates the relationship between CO and FP. The field research involved two phases. The first phase was exploratory. It aimed to identify metrics for the PIC construct still little explored in literature , and involved semi-structured interviews with executives from innovation area. The second phase carried out a cross-sectional survey involving 157 medium-sized Brazilian companies from industrial area, located in many regions of the country. After verifying the measures reliability and validity, the hierarchical regression and the Sobel Z test indicated the confirmation of all hypotheses presented. It was concluded that CO and PIC influence FP. CO also influences PIC. And, when TT levels are high, PIC mediates totally the relationship between CO and FP. Thus, the present study contributed to the academy in the way that it pointed a mediator between a strategic orientation and performance, suggested a concept of PIC and also validated a scale to measure it. These contributions encourage future studies to explore the identified relationships in order to find explanations for them as well as to investigate other mediators among these relationships.